2021
DOI: 10.1111/cen.14459
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between de novo lipogenesis and serum sex hormone binding globulin in humans

Abstract: Objective Obesity and liver fat are associated with decreased levels of serum sex hormone binding globulin (SHBG). Laboratory studies suggest that hepatic de novo lipogenesis (DNL) is involved in the downregulation of SHBG synthesis. The aim of the present study was to address the role of DNL on serum SHBG in humans. Design A cross‐sectional study examining the association between DNL, measured by stable isotopes, and serum SHBG, stratified by sex. Participants Healthy men (n = 34) and women (n = 21) were comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…Experimental studies have shown that hepatic de novo lipogenesis, which is increased in obesity and insulin resistance, 26 impairs SHBG synthesis in the liver 27 . We recently demonstrated that de novo lipogenesis, assessed by stable isotopes, is inversely associated with serum SHBG levels in women 28 . Hepatic de novo lipogenesis has also been associated with a disadvantageous lipid profile 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have shown that hepatic de novo lipogenesis, which is increased in obesity and insulin resistance, 26 impairs SHBG synthesis in the liver 27 . We recently demonstrated that de novo lipogenesis, assessed by stable isotopes, is inversely associated with serum SHBG levels in women 28 . Hepatic de novo lipogenesis has also been associated with a disadvantageous lipid profile 29 .…”
Section: Discussionmentioning
confidence: 99%
“…27 We recently demonstrated that de novo lipogenesis, assessed by stable isotopes, is inversely associated with serum SHBG levels in women. 28 Hepatic de novo lipogenesis has also been associated with a disadvantageous lipid profile. 29 The reduction in the strength of the association between SHBG and serum lipids after adjustment for BMI in the current study is in line with these previous observations and suggests that BMI is an important driver of the metabolic features and low serum SHBG levels that characterize PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Regression coefficients (β) and 95% confidence intervals (CI) are reported for the associations in the two groups combined. Of note, fasting serum insulin was unavailable in one GSD1a patient, and SFA was only measured in a subset of patients (n = 8) and controls (n = 5) (see "Methods" section) with serum SHBG levels, we could not assess the direction of the association [8]. This is of relevance, since in vitro experiments have also shown that SHBG can affect de novo lipogenesis [9].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and animal studies have shown that carbohydrate-induced de novo lipogenesis is one of the mechanisms involved in the downregulation of SHBG levels [7]. We have recently extrapolated these findings to humans, by showing that de novo lipogenesis, measured with stable isotopes, is inversely associated with serum SHBG levels [8]. However, given the observational nature of that study, we were unable to assess whether the effect of de novo lipogenesis on serum SHBG is causal.…”
Section: Introductionmentioning
confidence: 95%
“…Op die manier kunnen ze naar andere organen vervoerd worden, die het onder andere gebruiken als brandstof. Ten tweede leidt stapeling van vet in de lever ertoe dat er via een stofje -sex hormone binding globulin -ook meer actief testosteron in de bloedbaan terecht komt (Figuur 1) (8,9). Testosteron is het mannelijke hormoon.…”
Section: Wetenschappelijk Onderzoek Naar Type 2 Diabetes En Fructoses...unclassified